The outcome of Autogenous Venous Graft Vs Prosthetic Graft in Peripheral Arterial Disease- Study in Bangladesh - Mahmud, Mainul; Amin, Nur A Al; Hossain, Kamal; Ahmed, Uzzal; Rifat, Ashik Rahman; Hasan, Rakibul; Khan, Md Saif Ullah (University Heart Journal, 2024)
Graft insertion is a surgical intervention employed to address advanced stages of peripheral artery disease (PAD) or peripheral vascular disease (PVD). Peripheral artery disease (PAD) or peripheral vascular disease (PVD) refers to the narrowing or blockage of blood vessels, typically in the lower extremities resulting from the accumulation of fatty deposits (atherosclerosis). This condition leads to diminished blood flow to the affected regions. These symptoms may include leg pain, cramping, numbness, and, in severe instances, tissue damage and gangrene. Objective: This study aims to evaluate the surgical outcome of autogenous venous grafts and prosthetic grafts in peripheral arterial disease. Method: The cross-sectional study was conducted at Department of Vascular Surgery, Bangabandhu Sheikh Mujib Medical University & Enam Medical College Hospital, Savar, Dhaka - over two year from January 2021 to December 2022. This study represented patients who received surgical treatment for peripheral artery disorders using grafts, which could be either autogenous (vein) or prosthetic in nature. Results: Smoking, hypertension, and dyslipidemia were the main risk factors for PAD. The main indications of revascularization in our investigation were gangrene, critical limb ischemia, and limb salvage. In the case of a prosthetic graft, post-operative infection was higher. The other postoperative problems were thrombosisrelated occlusion and hemorrhage. Conclusion: Autogenous venous and prosthetic grafts can provide a bypass or supply blood flow to the damaged area during peripheral arterial disease (PAD) revascularization. The surgeon’s preference and the patient’s condition determine which graft type is used. In this study, prosthetic and autogenous venous grafts in PAD are compared. University Heart Journal 2023; 19(2): 55-60